The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/21645515.2017.1288769
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety evaluation of bivalent types 1 and 3 oral poliovirus vaccine by comparing different poliomyelitis vaccination schedules in China: A randomized controlled non-inferiority clinical trial

Abstract: Background: The type 2 component of the oral poliovirus vaccine is targeted for global withdrawal through a switch from the trivalent oral poliovirus vaccine (tOPV) to a bivalent oral poliovirus vaccine (bOPV). The switch is intended to prevent paralytic polio caused by circulating vaccine-derived poliovirus type 2. We aimed to assess the immunogenicity and safety profile of 6 vaccination schedules with different sequential doses of inactivated poliovirus vaccine (IPV), tOPV, or bOPV.Methods: A randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The studies in Chile [ 7 ], India [ 8 ], and 4 Latin America countries [ 10 , 11 ] included groups that received bOPV + 2 IPV doses, each of which achieved seroconversion of ≥96% for type 2 and >99% for types 1 and 3 ( Table 2 ). The study in China [ 12 ] with patients given 2 IPV doses followed by a single bOPV achieved seroconversion rates of 94.2%, 82.6%, and 97.7% for types 1, 2, and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies in Chile [ 7 ], India [ 8 ], and 4 Latin America countries [ 10 , 11 ] included groups that received bOPV + 2 IPV doses, each of which achieved seroconversion of ≥96% for type 2 and >99% for types 1 and 3 ( Table 2 ). The study in China [ 12 ] with patients given 2 IPV doses followed by a single bOPV achieved seroconversion rates of 94.2%, 82.6%, and 97.7% for types 1, 2, and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In Pakistan, a birth dose of bOPV followed by bOPV at 6–10–14 weeks and 1 dose of IPV at 14 weeks produced low type 2 seroconversion rates (51.3%), possibly due to high levels of maternal antibodies at baseline and widespread (19.4%) passive exposure to circulating type 2 vaccine viruses confounding the impact of IPV at 14 weeks. In contrast, the Chile and China studies evaluating sequential schedules [ 7 , 12 ], where IPV was given at 8 or 10 weeks without concomitant bOPV, reported type 2 seroconversion rates of 77.4% and 55.8%, respectively. Studies that evaluated the 2-dose impact of IPV (India, Chile, Latin America) reported uniformly high seroconversion rates of ≥96% for type 2 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PV type 1-3, belonging to EV-C, is notable as the pathogen of poliomyelitis (polio) [17,43]. We observed that all the patients associated with PV presented typical clinical manifestation of HFMD, such as skin rashes on hands and feet, and the age with serotypes of the affected associated with the PV inoculation [44,45]. However, the vaccination records of eight patients were unclear and further studies are needed.…”
Section: Discussionmentioning
confidence: 97%
“…Vaccination with sIPV and wIPV were provided to infants as the first dose of polio vaccine routine schedule for free. Although studies have shown that sequential schedules of wIPV with bOPV [4][5][6][7] and sIPV with tOPV [8][9][10] are sufficient for immunization, the immunogenicity of sequential schedules of different virus strain IPVs with bOPV remains unclear. Differences in the vaccines or the populations might affect immunogenicity.…”
Section: Introductionmentioning
confidence: 99%